Circuitos comunicacionais ativados pela autorreferência didática no jornalismo: o caso do profissão repórter - Klein, Eloísa Joseane Da Cunha (Universidade do Vale do Rio dos Sinos, 2012)
This research is defined as a case study which takes as its central object the television programme “Profissão Repórter”, aired weekly since 2008 by Rede Globo, on Tuesdays, in the range of 11:30 hours PM, before the last television newscast. For the case study of “Profissão Repórter”, the research studies the journalism and the social interactions articulated in the process of transformation of society in mediatization. The research is empirically based, and highlights specific questions and transversal aspects, which allow inferences about the social context and the dynamic insertion in television. “Profissão Repórter” presents itself as appropriate to observe the changes in the characterization of journalistic genres, taking into account its overlapping with entertainment genres. The uniqueness of Profissão Repórter is a structural model of self-reference, addressing didactic elements on the journalistic activity to the viewer.
Keywords: Profissão Repórter; Autorreferencialidade; Circulação social; Midiatização; Self-reference; Questões didáticas; Social Circuits; Mediatization; Didactic questions; ACCNPQ::Ciências Sociais Aplicadas::Comunicação